Оптимізація ціноутворення на основі моделей інтелектуального аналізу даних - Чорноус, Галина Олександрівна; Рибальченко, С. (Київський національний університет імені Тараса Шевченка, 2015)
У статті проаналізовано питання ефективного використання інформаційного ресурсу підприємств щодо формування оптимальних цін на товар чи послугу. Запропоновано підхід до розв'язання задачі оптимізації ціни для різних груп споживачів на основі гібридної моделі інтелектуального аналізу даних, що містить набір штучних нейронних мереж. Продемонстровано варіант упровадження запропонованого підходу на прикладі підприємства роздрібної торгівлі.

The purpose of this paper is to develop and implement an approach for solving the optimization problem in the retailers goods market and different consumers groups based on a hybrid model of intelligent data analysis. It is revealed that for each consumer type product information array formed consisting of the factors values that affect the company revenue. An example of the optimal prices hybrid model synthesis in the product (beer) market and grocery stores network were considered. Solving the problem of optimizing product prices by consumer groups was implemented in two stages: first constructed interpolation function of consumer demand each group, and then solve the problem of optimizing implicitly given function. Demand function obtained by artificial neural networks.
Pricing Optimization Based on Intelligent Data Analysis Model
Keywords: ціноутворення; оптимізація; інтелектуальний аналіз даних; штучна нейронна мережа; гібридна модель; pricing; optimization; intelligent data analysis; artificial neural network; hybrid model